The good, the bad and the outcast - Lunaček, Izar T. (Studia mythologica Slavica, 2014)
This article examines the common traits of popular folk heroes in order to demonstrate their common misconception as powerful individuals fighting against an evil threatening their community. In fact, folk heroes often prove to be tiny, seemingly insignificant aberrations the system, who gain their special status by rebelling against the rules governing their respective societies, thus becoming radical social outcasts whose characters border on the monstrous. Even when heroes are explicitly pitted against apparently evil monsters threatening their societies, their relationships with monsters prove to be highly ambivalent: they have to take on some of the monsters' qualities in order to be able to beat them and the later occasionally even prove to be uncomfortably related to them. In order to proveits point, this paper examines two of the most popular folk heroes in Slovenia: Martin Krpan and King Matja as well as a host of heroes and tricksters from across the globe, paying special attention to the worldwide motif of the miser and the thief, where the roles of hero and monster hold a particularly high degree of exchangeability.
Keywords: mitologija; mythology; ljudska kultura; ljudske legende; dobro in zlo; heroji; pošasti; izobčenci